Left atrial scarring and conduction velocity dynamics: Rate dependent conduction slowing predicts sites of localized reentrant atrial tachycardias. (1st March 2019) - Honarbakhsh, S.; Schilling, R.J.; Orini, M.; Providencia, R.; Finlay, M.; Keating, E.; Lambiase, P.D.; Chow, A.; Earley, M.J.; Sporton, S.; Hunter, R.J.
Abstract: Background: Low voltage zones (LVZs) are associated with conduction velocity (CV) slowing. Rate-dependent CV slowing may play a role in reentry mechanisms. Methods: Patients undergoing catheter ablation for AT were enrolled. Aim was to assess the relationship between rate-dependent CV slowing and sites of localized reentrant atrial tachycardias (AT). On a bipolar voltage map regions were defined as non-LVZs [≥0.5 mV], LVZs [0.2–0.5 mV] and very-LVZs [<0.2 mV]. Unipolar electrograms were recorded with a 64-pole basket catheter during uninterrupted atrial pacing at four pacing intervals (PIs) during sinus rhythm. CVs were measured between pole pairs along the wavefront path. Sites of rate-dependent CV slowing were defined as exhibiting a reduction in CV between PI = 600 ms and 250 ms of ≥20% more than the mean CV reduction seen between these PIs for that voltage zone. Rate-dependent CV slowing sites were correlated to sites of localized reentrant ATs as confirmed with conventional mapping, entrainment and response to ablation. Results: Eighteen patients were included (63 ± 10 years). Mean CV at 600 ms was 1.53 ± 0.19 m/s in non-LVZs, 1.14 ± 0.15 m/s in LVZs, and 0.73 ± 0.13 m/s in very-LVZs respectively ( p  < 0.001). Rate-dependent CV slowing sites were predominantly in LVZs [0.2–0.5 mV] (74.4 ± 10.3%; p  < 0.001). Localized reentrant ATs were mapped to these sites in 81.8% of cases (sensitivity 81.8%, 95% CI 48.2–97.9% and specificity 83.9%, 95% CI 81.8–86.0%). Macro-reentrant or focal ATs were not mapped to sites of rate-dependent CV slowing. Conclusions: Rate-dependent CV slowing sites are predominantly confined to LVZs [0.2–0.5 mV] and the resultant CV heterogeneity may promote reentry mechanisms. These may represent a novel adjunctive target for AT ablation. Highlights: CVs and CV dynamics in the human LA are dependent on the underlying bipolar voltage. Rate-dependent CV slowing sites are predominantly confined to LVZs [0.2–0.5 mV]. Rate-dependent CV slowing sites can predict localized reentrant ATs.